Dialysis Dependency at Discharge in De Novo ANCA Associated Renal Limited Vasculitis: Should We Avoid Further Immunosuppression? - Rui Filipe Nogueira; Nuno Afonso Oliveira; Margarida Gaudêncio; Ana Belmira; Rui Alves (Publicações Ciência e Vida, 2022)
Introduction: ANCA associated vasculitis commonly affects the kidneys. The intense inflammatory damage disrupts the glomerular architecture. Induction immunosuppressive therapy is responsible for a large part of the morbidity and mortality of these patients, due to infectious complications. This highlights the importance of defining risk factors associated with a worse renal prognosis in order to select the patients who would benefit the most from immunosuppressive therapy when it comes to renal limited vasculitis. Methods: Retrospective collection of data from patients admitted to the Coimbra's University Hospital Nephrology Department with the diagnosis of de novo ANCA vasculitis, between 01-06-2009 and 01-06-2019. Data were analysed with SPSS v26® using parametric and nonparametric tests, Kaplan Meyer survival and ROC curve analysis. Results: There were 81 cases of de novo vasculitis, mainly due to anti-MPO antibody associated vasculitis (N=69; 85.2%). Mean age at diagnosis was 67.4 ± 15.7 years and most patients were male (N=47; 58%). At admission, patients had a mean serum creatinine (sCr) of 6.8 ± 4.0 mg/dL. Dialysis was required in 23 (28.4%) patients at admission and 44.4% were dependent on renal replacement therapy at discharge. Among dialysis-dependent patients at discharge treated with immunosuppression for at least 3 months (N=15) we observed partial kidney recovery in 2 (13.3%). Deaths were mostly (N=8/11; 72.7%) caused by infections. Discussion: Our results call into question the need for aggressive induction treatment in dialysis-dependent patients without extrarenal manifestations.